THE EFFECTIVENESS OF QUESTION ANSWER RELATIONSHIP TECHNIQUE IN TEACHING READING COMPREHENSION ON NARRATIVE TEXT - Sari, Rika; Sada, Clarry; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The objective of this research was to find out the effectiveness of using Question Answer Relationship (QAR) Technique and how effectives is the use of QAR in teaching reading comprehension on narrative text to the tenth year students of â€œSMAN 1 Sungai Rayaâ€ in Academic Year 2014/205. This research was a pre-experimental research with one group pre test and post test design. The sample of this research was XJ which consist of 38 students. Â Based on the research findings, the use of QAR technique is effective to teach reading comprehension on narrative text. The mean score of pre test is 61.44 and the mean score of post test is 71.44. The interval score of the mean score of pre test and post test is 10. It means that there was improvement on studentsâ€™ score in reading comprehension on narrative text. The data calculation also shows the effect size is 1.19 greater than 0.8 (1.19>0.8). It is categorized as large effect. It indicates that the implementation of QAR technique was effective in teaching reading comprehension on narrative text. Â Keywords: Question Answer Relationship Technique, Narrative Text Abstract: Tujuan dari penelitian ini adalah untuk menemukan keefektifan dari penggunaan Teknik Question Answer Relationship (QAR) dan seberapa efektifkah teknik tersebut dalam mengajarkan pemahaman membaca teks narative pada siswa kelas 10 di SMA Negeri 1 Sungai Raya pada tahun ajaran 2014/2015.Â Penelitian ini adalah experimental research dengan model grup pre test dan post test. Sampel penelitian ini adalah kelasÂ XJ yang terdiri dari 38 siswa. Berdasarkan hasil penelitian, penggunaan teknik QAR efektif dalam mengajarkan pemahaman membaca teks narrative. Nilai rata-rata dari pre test adalah 61.44 dan nilai rata-rata dari post test adalah 71.44. Perbedaan antara nilai rata-rata dari pre test dan post test adalah 10. Hal ini menunjukan bahwa adanya peningkatanÂ pada nilai pemahaman membaca siswa pada teks narrative. Hasil perhitungan data juga menunjukan bahwa tingkat keefektifannya adalah 1.19 yang artinya lebih besar dari 0.08 (1.19>0.08). Hal itu berarti tingkat keefektifannya tinggi. Jadi, hal itu menunjukan bahwa pengimplementasian dari teknik QAR adalah efektif dalam mengajarkan pemahaman membaca pada teks naratif. Â Kata kunci: Teknik Question Answer Relationship, Teks naratif Â Â